2013
DOI: 10.1016/j.ijdevneu.2013.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Critical role for inhibitory neurons in modulation of synaptic signaling in ex vivo neuronal networks

Abstract: A number of laboratories have modeled aspects of synaptic plasticity using neuronal networks established on micro-electrode arrays. Such studies demonstrate that external stimulation can increase or hasten maturation of network signaling as evidenced an increase in complex bursts. Herein, we demonstrate that repetitive stimulation with a recorded synaptic signal was capable of increasing overall signaling, including the percentage of bursts, over a 5-day period, but that this increase was completely prevented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 41 publications
(59 reference statements)
5
21
0
Order By: Relevance
“…This unique model can be analyzed in detail, and/or expanded upon to encompass additional functionality. Prior studies demonstrated that these networks display alterations in signaling consistent with long-term potentiation following repetitive stimulation with the same digitized synaptic signal utilized herein [4,6]. Embodiment of the neuronal network as described herein provides the unique opportunity for future studies of long-term potentiation by biological neuronal networks in an environmental context.…”
Section: Discussionmentioning
confidence: 85%
“…This unique model can be analyzed in detail, and/or expanded upon to encompass additional functionality. Prior studies demonstrated that these networks display alterations in signaling consistent with long-term potentiation following repetitive stimulation with the same digitized synaptic signal utilized herein [4,6]. Embodiment of the neuronal network as described herein provides the unique opportunity for future studies of long-term potentiation by biological neuronal networks in an environmental context.…”
Section: Discussionmentioning
confidence: 85%
“…Monitoring of signal patterns further demonstrated that bursts appeared relatively early and did not change in frequency during development, but that higher‐amplitude individual spikes underwent a developmental decline. The more detailed analyses presented herein, coupled with the resurgence of high‐amplitude spikes following suppression of inhibitory activity, suggested progressive elimination of spikes played a major role in the establishment of the mature signaling pattern (Zemianek et al, 2013a). Our studies of individual signal patterns herein further extend these considerations by demonstrating that suppression of inhibitory activity shifts the predominance of signals toward those containing relatively high‐amplitude spikes.…”
Section: Discussionmentioning
confidence: 89%
“…Prior studies from multiple laboratories demonstrate that cultured neurons initially elaborate predominantly high‐amplitude spikes, and by >30 days after plating establish a so‐called mature pattern of signals that consists of complex bursts of varying amplitude and duration along with a relatively fewer spikes (van Pelt et al, 2004a,b; Madhavan et al, 2005; Wagenaar et al, 2006; Ikegaya et al, 2008; Chiappalone et al, 2009; Zemianek et al, 2012a,b, 2013a,b). We first confirmed that this was also the case in our current networks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations